Electrochemiluminescence-based high-sensitivity detection method for early aging of aromatic polymer
The free radicals generated by aging of aromatic polymers are detected by electrochemiluminescence, which solves the problem of low detection sensitivity of aging behavior in the prior art, and realizes early and highly sensitive detection of aging behavior of aromatic polymers, with fast and reliable advantages.
Patent Information
- Application Number
- CN202510045024.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-10
AI Technical Summary
The prior art is difficult to detect the aging behavior of aromatic polymers in high sensitivity and early stages. The traditional method has low sensitivity and requires long-term aging and degradation to capture obvious signal changes.
The carbon-center radicals and reactive oxygen radicals generated by aging of aromatic polymers are used to detect the aging behavior of materials under different aging conditions by selecting suitable electrochemiluminescence probes and workstations.
It realizes early and highly sensitive detection of aging behavior of aromatic polymers, and can detect aging behavior in the early stages of aging, solving the problems of poor sensitivity and low practicality of traditional methods, and has the advantages of rapid and reliable.
Smart Images

Figure HDA0005238135760000011 
Figure HDA0005238135760000012 
Figure HDA0005238135760000021
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of material aging detection, and in particular relates to a highly sensitive and rapid detection method for early aging behavior of aromatic polymer materials by using electrochemical luminescence. Background Art
[0002] Aromatic polymer materials have good rigidity due to the abundant benzene ring structure in their structure, and thus have a wide range of applications in electronic devices, optical instruments and other fields. However, due to the absorption of ultraviolet rays by benzene rings under light radiation, it becomes an initiator of photodegradation of aromatic polymers. Therefore, aromatic polymers will generate carbon-centered free radicals under light radiation, which will further promote the generation of hydroxyl radicals (·OH) and superoxide anion radicals (O2 ·- ) and other highly active substances. In addition, due to the rich benzene ring structure of aromatic polymers, carbon-centered free radicals can be stabilized and accumulated continuously, accelerating the chain reaction of polymer aging and degradation, causing polymer structure degradation and performance failure. Therefore, it is urgent to accurately identify and evaluate the free radicals generated by polymers in the early stage of polymer aging in order to reveal the degradation mechanism of polymers and realize the use management of polymers.
[0003] Traditionally, free radical detection during polymer aging is mainly based on electron spin resonance. However, the sensitivity of electron spin resonance is limited, and it takes a long period of aging degradation to capture obvious signal changes, which limits the high-sensitivity and early detection of polymer aging degradation.
[0004] Electrochemiluminescence is widely used for the evaluation of material structure and reaction process due to its high sensitivity. The method of the present invention is based on the electrochemiluminescence method to perform early and highly sensitive detection of aromatic polymer aging. Since the aging of aromatic polymers generates carbon-centered free radicals and promotes the generation of active oxygen free radicals, the electrochemiluminescence signal increases significantly. Therefore, the aging behavior of aromatic polymers can be detected with high sensitivity and accuracy through the changes in the electrochemiluminescence signal. This method has high sensitivity and good accuracy, and can be used for early detection of aromatic polymer aging, providing new methods and strategies for the study of its aging and degradation mechanism. Summary of the invention
[0005] Based on the principle that aromatic polymers generate carbon-centered free radicals during aging and promote the generation of active oxygen free radicals, in order to overcome the difficulties of the prior art, the present invention provides a highly sensitive early detection method for the aging behavior of aromatic polymers.
[0006] The technical solution of the present invention is: for the carbon-centered free radicals, hydroxyl free radicals, superoxide anion free radicals, etc. generated by aging of aromatic polymer materials under conditions of light, heat, stress, oxygen, etc., a suitable electrochemiluminescence luminescent probe is selected, and an electrochemiluminescence workstation is used to perform high-sensitivity detection of the early aging behavior of aromatic polymers, revealing the various types of free radicals generated during the reaction process and their changes.
[0007] This method is suitable for the detection of aging behaviors of various aromatic polymer materials under different aging conditions. The detection targets are carbon-centered free radicals, hydroxyl radicals, superoxide anion radicals, etc. It is applicable to the aging process of various aromatic polymers. The method has wide applicability to various materials and is easy to operate.
[0008] This method has high detection sensitivity. This method can detect the aging behavior of aromatic polymers in the early stage of aging, while the traditional method of chain break detection of polymer materials requires long-term aging treatment. This method effectively solves the limitations of traditional methods such as poor sensitivity and low practicality, and has the advantages of being fast and reliable.
[0009] A highly sensitive detection method for aromatic polymer aging based on electrochemiluminescence is characterized by comprising the following steps:
[0010] (1) Preparation of aromatic polymer films
[0011] Aromatic polymer film materials are constructed by hot pressing, solvent evaporation, blow molding, etc. Taking the solvent evaporation method as an example, aromatic polymer particles can be dissolved in a certain concentration of organic solvent, transferred to a crystallization dish, and vacuum dried at 40-100°C.
[0012] (2) Aging of aromatic polymer films
[0013] Aromatic polymer films were aged using light, heat, water, oxygen, stress and other conditions; the wavelength of light aging radiation was 280-400nm, and the irradiation intensity was 0.5-2.0W / m 2 , the temperature is 40-120℃, the oxygen content is 0%-100%, the water vapor content is 20%-80%, the stress is 0.5-10MPa; the aging time is 0-10 days, and the polymer material is aged for different time periods;
[0014] (3) Deposition of aromatic polymer films on ITO electrodes
[0015] The ITO electrode is ultrasonically cleaned in water (30 min), ethanol (30 min) and water (15 min) in turn. The aromatic polymer film before and after aging is dissolved, and then different ITO electrodes are immersed in the corresponding aromatic polymer film solutions before and after aging for 10-60 seconds, and after drying in air, the aromatic polymer films before and after aging deposited on the ITO are obtained respectively; the aging can be different aging conditions, such as different specific conditions such as light, heat, water, oxygen, stress, etc. in step (2), and even different parameters corresponding to different aging conditions, different aging time, etc.;
[0016] (4) Electrochemiluminescence test
[0017] The electrochemiluminescence test is performed using a three-electrode system, with a Pt electrode as a counter electrode, an Ag / AgCl electrode as a reference electrode, an ITO electrode corresponding to the aromatic polymer film before and after deposition aging as a working electrode, and a test solution as an optical probe solution, and the electrochemiluminescence signal is recorded; for example, a 50-500 μmol / L luminol solution is selected, 0.1 mol / L phosphate buffered saline (PBS, pH=7.4) is added, the scanning potential range is -0.8 to +1.2 V, the scanning rate is 0.02-0.2 V / s, and the electrochemiluminescence signal is recorded;
[0018] (5) Electrochemiluminescence signal analysis
[0019] The electrochemiluminescence signals of aromatic polymer films aged under different conditions and for different time periods were analyzed by electrochemiluminescence measurement.
[0020] By performing electrochemiluminescence detection and electrochemiluminescence signal analysis in different atmospheres (such as atmospheres with different oxygen contents, etc.), the corresponding atmosphere with strong signal is selected according to the change of electrochemiluminescence signal in different atmospheres; the electrochemiluminescence signal analysis includes the analysis of the change of electrochemiluminescence signal of the aromatic polymer film before aging and after aging corresponding to different aging conditions. The aging of the aromatic polymer film can be judged and explored according to the comparison of the strength of the signal. The stronger the signal, the more serious the aging;
[0021] (6) Methyl blue was used to semi-quantitatively analyze the content of hydroxyl radicals in the system, and nitro blue tetrazolium chloride was used to semi-quantitatively analyze the content of superoxide anion radicals in the system. The generation of hydroxyl radicals and superoxide anion radicals during the aging of aromatic polymers under different aging conditions, as well as the changes in the content of hydroxyl radicals and the content of superoxide anion radicals were studied.
[0022] Highly sensitive detection of the early aging behavior of aromatic polymers is carried out, while further revealing the various types and changes of free radicals generated during the reaction process.
[0023] It also further includes the following:
[0024] Aging verification of aromatic polymer films: Gel permeation chromatography was used to measure the number average molecular weight and weight average molecular weight of the aged films to verify the structural deterioration and degradation behavior of the films.
[0025] The aromatic polymer selected in step (1) includes but is not limited to one or more of polystyrene, aromatic polycarbonate, aromatic polyamide, aromatic polyester, polyarylate, and aromatic ketone polymer.
[0026] Aromatic polymers generate carbon-centered free radicals after aging treatment, and these carbon-centered free radicals promote the generation of active oxygen free radicals such as hydroxyl free radicals and superoxide anion free radicals. The present invention uses an electrochemiluminescent probe to perform highly sensitive electrochemiluminescent detection of free radicals generated after aromatic polymer aging. The method developed by the present invention is designed based on the universal principle of aromatic polymer aging reactions, and can realize the aging behavior detection of various aromatic polymers, with the characteristics of rapid detection, accurate results, strong repeatability, high sensitivity, high practicality, and wide applicability. The present invention successfully realizes the early detection of aging of aromatic polymer materials, and provides a new means for revealing its aging mechanism and monitoring aging behavior. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The electrochemiluminescence signal value changes after multiple repeated scans using luminol as the electrochemiluminescence probe.
[0028] Figure 2 Electrochemiluminescence signal values of polystyrene (PS) film after photoaging for 0, 2, 4, 6, 8, 10, and 12 hours.
[0029] Figure 3 The electrochemiluminescence signal of the PS film after photoaging for 0, 4, 8, and 12 hours varies with voltage.
[0030] Figure 4 The electrochemiluminescence signal values of the unaged (pristine) and light-aged 12h (P-12h) PS films in air and nitrogen.
[0031] Figure 5 The UV-visible absorption spectra of methyl blue and the statistics of methyl blue quenching ratio of PS films without aging (pristine) and photoaging for 12h (P-12h) after electrochemical testing.
[0032] Figure 6 The UV-visible absorption spectra and changes of nitro blue tetrazolium chloride in PS films without aging (pristine) and after 12h of light aging (P-12h) after electrochemical testing are shown.
[0033] Figure 7 These are electron spin resonance images of PS films that were not aged (pristine), photoaged for 12 h (P-12 h), photoaged for 3 days (P-3 d), and photoaged for 6 days (P-6 d), wherein (A) is the determination of carbon-centered free radicals, (B) is the determination of hydroxyl radicals, and (C) is the determination of superoxide anion radicals.
[0034] Figure 8 The molecular weight change diagram of PS film without aging (pristine), photoaging for 12h (P-12h), photoaging for 3 days (P-3d) and photoaging for 6 days (P-6d). DETAILED DESCRIPTION
[0035] The present invention will be further described below in conjunction with examples, but the present invention is not limited to the following examples.
[0036] Embodiment 1:
[0037] (1) Preparation of polystyrene (PS) film
[0038] 4.00 g of PS particles were dissolved in dichloromethane with a concentration of 10 wt %, transferred to a 12 cm crystallization dish at room temperature, and dried in vacuum at 60° C. overnight to obtain a PS film.
[0039] (2) Photoaging of PS films
[0040] The prepared PS film was subjected to light aging treatment for different time periods on an accelerated aging device with an ultraviolet irradiation intensity of 1.0 W / m 2 , wavelength of 340 nm, temperature of 60 ° C. PS films were treated under light irradiation for 0-12 h, marked as Px h.
[0041] (3) Deposition of PS film on ITO electrode
[0042] The ITO electrode was ultrasonically cleaned in water (30 min), ethanol (30 min) and water (15 min) in sequence. The PS film before and after light aging treatment was dissolved in dichloromethane with a concentration of 7.5 wt%. The ITO electrode was then immersed in the PS solution for 10 s and dried in air to obtain the PS film deposited on the ITO.
[0043] (4) Electrochemiluminescence test
[0044] A three-electrode system was used for electrochemiluminescence testing. The Pt electrode was used as the counter electrode, the Ag / AgCl electrode was used as the reference electrode, and the PS-deposited ITO electrode was used as the working electrode. The test solution used was a 300μmol / L luminol solution, with 0.1mol / L phosphate buffered saline (PBS, pH=7.4) added. The scanning potential range was -0.8 to +1.2V, and the scanning rate was 0.1V / s. The electrochemiluminescence instrument photomultiplier tube voltage was set to -900V, and the electrochemiluminescence signal was recorded. Repeatability tests were performed, such as Figure 1 As shown, the electrochemiluminescence signal was stable after 9 cycles, indicating that the electrochemiluminescence analysis method used had high accuracy and good repeatability.
[0045] (5) Analysis of electrochemiluminescence signals of photo-aged PS films
[0046] Electrochemiluminescence was measured on PS films treated with light aging for different times, such as Figure 2 The normalized changes of the electrochemiluminescence signal are shown in Figure 2. After light aging treatment, the electrochemiluminescence signal value of the PS film continued to increase, and after 12 hours of treatment, its intensity was twice that of the untreated film, indicating that electrochemiluminescence can be used to detect the light aging behavior of the PS film.
[0047] The electrochemiluminescence-voltage change diagram is analyzed, such as Figure 2 As shown, it can be observed that an electrochemical oxidation peak is generated at about 0.8 V, which is attributed to the oxidation peak of the probe molecule luminol.
[0048] (6) Analysis of the electrochemiluminescence enhancement principle of photo-aged PS films
[0049] By analyzing the electrochemiluminescence signals of PS films in different atmospheres, the principle of electrochemiluminescence enhancement of PS films after light aging was explored. Figure 3 As shown in the figure, the signal values of the PS films without aging (pristine) and after 12h of light aging (P-12h) in air are higher, while the signal values in nitrogen are significantly reduced, indicating the important influence of oxygen on the electrochemiluminescence signal. Among them, the signal value of P-12h in nitrogen is quenched by 96% compared with that in air.
[0050] Methyl blue (3 mg / L) was used to semi-quantitatively analyze the content of hydroxyl radicals in the system, and its absorbance was calculated. The results showed that the degradation effect of methyl blue by P-12h after aging was better ( Figure 5 ), indicating that it produces more hydroxyl radicals. Nitro blue tetrazolium chloride (5mmol / L) was used to semi-quantitatively analyze the content of superoxide anion radicals in the system, and its absorbance was calculated. The results showed that the absorbance obtained by aging P-12h was higher, about 0.09 ( Figure 6), indicating that it produces more superoxide anion radicals.
[0051] The above results show that the PS film produces a large number of active oxygen free radicals under light treatment, which directly leads to a significant increase in the electrochemiluminescence signal.
[0052] (7) Free radical verification of photo-aged PS films
[0053] 150 mg of PS film was cut into pieces and placed in a quartz tube for electron spin resonance measurement of solid samples. The carbon-centered free radical was at a g value of 2.004. However, for the early aged PS film, no signal was detected; a weak signal appeared only after 3 days of aging, and a significant signal only appeared after 6 days of aging ( Figure 7 A). The above results indicate that carbon-centered free radicals are generated in the aged PS film, but due to the limited sensitivity of electron spin resonance, they can only be detected after long-term aging.
[0054] DMPO water or DMPO / DMSO solution was further used to capture OH or O2 ·- OH or O2 can be detected in the PS film after aging for 12 hours. ·- , verifying the accuracy of electrochemiluminescence detection.
[0055] Therefore, we can infer that the carbon-centered free radicals generated by the aging of the PS film exist and promote the OH or O ·- The generation of luminol leads to the enhancement of luminol luminescence, showing an increasing electrochemiluminescence signal, which realizes the early and highly sensitive detection of the photoaging behavior of PS film.
[0056] (8) PS film aging verification
[0057] The number average molecular weight and weight average molecular weight of the aged PS membrane were further determined by gel permeation chromatography. Figure 8 As shown in the figure, the molecular weight change was basically undetectable before 12 hours of aging. However, the change in molecular weight after aging for 3-6 days could be determined by gel permeation chromatography. The above results show that the light aging treatment caused the structural deterioration and degradation of the PS membrane.
Claims
1. A highly sensitive detection method for aromatic polymer aging based on electrochemiluminescence, characterized in that: The following steps are involved: (1) Preparation of aromatic polymer films (2) Aging of aromatic polymer films (3) Deposition of aromatic polymer films on ITO electrodes The ITO electrode is ultrasonically cleaned in water, ethanol and water in turn; the aromatic polymer films before and after aging are dissolved, and then different ITO electrodes are immersed in the corresponding aromatic polymer film solutions before and after aging for 10-60 seconds, and the aromatic polymer films before and after aging deposited on the ITO are obtained after drying in air; (4) Electrochemiluminescence test The electrochemiluminescence test was carried out using a three-electrode system, with a Pt electrode as the counter electrode, an Ag / AgCl electrode as the reference electrode, an ITO electrode corresponding to the aromatic polymer film before and after deposition and aging as the working electrode, and a test solution as the optical probe solution to record the electrochemiluminescence signal; (5) Electrochemiluminescence signal analysis The electrochemiluminescence signals of aromatic polymer films aged under different conditions and for different time periods were analyzed by electrochemiluminescence measurement. By performing electrochemiluminescence detection and electrochemiluminescence signal analysis in different atmospheres (such as atmospheres with different oxygen contents, etc.), the corresponding atmosphere with strong signal is selected according to the change of electrochemiluminescence signal in different atmospheres; the electrochemiluminescence signal analysis includes the analysis of the change of electrochemiluminescence signal of the aromatic polymer film before aging and after aging corresponding to different aging conditions. The aging of the aromatic polymer film can be judged and explored according to the comparison of the strength of the signal. The stronger the signal, the more serious the aging; (6) Methyl blue was used to semi-quantitatively analyze the content of hydroxyl radicals in the system, and nitro blue tetrazolium chloride was used to semi-quantitatively analyze the content of superoxide anion radicals in the system. The generation of hydroxyl radicals and superoxide anion radicals during the aging of aromatic polymers under different aging conditions, as well as the changes in the content of hydroxyl radicals and the content of superoxide anion radicals were studied.
2. The method according to claim 1, characterized in that The preparation of aromatic polymer film adopts methods such as hot pressing, solvent evaporation, and blow molding to construct aromatic polymer film materials; taking the solvent evaporation method as an example, the aromatic polymer particles can be dissolved in a certain concentration of organic solvent, transferred to a crystallization dish, and vacuum dried at 40-100°C.
3. The method according to claim 1, characterized in that Aging of aromatic polymer films: corresponds to the aging of aromatic polymer films by light, heat, water, oxygen, stress and other conditions; the wavelength of light aging radiation is 280-400nm, and the irradiation intensity is 0.5-2.0W / m 2 , temperature is 40-120℃, oxygen content is 0%-100%, water vapor content is 20%-80%, and stress is 0.5-10MPa.
4. The method according to claim 3, characterized in that The aging described in step (3) can be different aging conditions, such as different specific conditions such as light, heat, water, oxygen, stress, etc. in step (2), and even different parameters corresponding to different aging conditions, different aging times, etc.
5. The method according to claim 1, characterized in that Step (4) Select an electrochemiluminescent probe, including but not limited to luminol, etc. The test solution is 50-500 μmol / L luminol solution, 0.1 mol / L phosphate buffered saline is added, the scanning potential range is -0.8 to +1.2 V, the scanning rate is 0.02-0.2 V / s, and the electrochemiluminescent signal is recorded.
6. The method according to claim 1, characterized in that Highly sensitive detection of the early aging behavior of aromatic polymers is carried out, while further revealing the various types and changes of free radicals generated during the reaction process.
7. The method according to claim 1, characterized in that It also further includes the following: Aging verification of aromatic polymer films: using gel permeation chromatography to measure the number average molecular weight and weight average molecular weight of the aged film to verify the structural deterioration and degradation behavior of the film.
8. The method according to claim 1, wherein the aromatic polymer comprises a polystyrene (PS) film.
9. The method according to any one of claims 1 to 8 is applied to aging monitoring and failure analysis of materials.
Citation Information
Patent Citations
Polymer material aging detection and process analysis method
CN111562241A
Polymer composition with improved ageing resistance
EP1849824A1
Method for producing electrochemiluminescence nanoprobe, electrochemiluminescence nanoprobe, electrochemiluminescence sensor, electrochemiluminescence detection method, and kit for electrochemiluminescence detection
US20240425751A1